Evaluation of routine blood sugar screening Program as an effort to prevent Diabetes in the community - Hutapea, Dwight Mahaputera Marulitua; Hutapea, Kimberley Maharani Maulibulung (PT. Anagata Sembagi Education, 2025)
This study aims to evaluate the effectiveness of routine blood sugar screening programs in early detection of diabetes and preventing long-term complications in the community. This screening Program has proven effective in detecting cases of diabetes at an early stage, but the level of community participation still needs to be improved. Factors such as people's knowledge of diabetes, accessibility of health services, and social and economic conditions influence participation in the program. In addition, the challenges faced include limited infrastructure, a shortage of trained medical personnel, and the cost of screening which is an obstacle for some communities. Although this screening encourages positive behavioral changes, such as healthy eating and exercise, ongoing support through education and supervision is needed to ensure long-term changes. The study recommends improving access and quality of services, as well as health policies that support the sustainability and expansion of routine blood sugar screening programs.